Trait–environment interactions influence tree planting success in Peruvian tropical dry forests - Goossens, Willem; Fremout, Tobias; Muys, Bart; Soto Quispe, Juan C.; van Meerbeek, Koenraad; Maes, Sybryn L. (Wiley, 2025)
Tropical dry forests (TDFs) are among the most endangered ecosystems globally, despite their critical socio‐ecological importance. In recent decades, tree planting initiatives have been widely implemented to restore these forests, yielding mixed results. To enhance restoration effectiveness, it is imperative to adopt a predictive approach, focusing on the drivers of seedling performance and how these drivers interact. This study explores how functional traits of planted tree species interact with site environmental conditions to influence seedling survival and growth rates across nine restoration sites of varying ages and climatic conditions within the Peruvian Tumbes‐Piura TDFs. While the widely accepted resource‐use theory predicts that acquisitive species—focusing on the fast retrieval of resources and characterized by higher specific leaf area and lower wood density—achieve high growth rates in resource‐rich environments but experience declines in growth rates under resource‐limited conditions, we found that acquisitive species maintained their high growth rates along the environmental gradients. In contrast, conservative species, expected to be less sensitive to resource variability, exhibited marked declines in growth when water or nutrient availability decreased. Additionally, nitrogen‐fixing species did not outperform non‐fixers in growth or survival, indicating that nitrogen fixation alone does not confer a consistent advantage in early restoration. Overall, our findings highlight the importance of trait–environment interactions in tree planting performance and underscore the need to align species selection and management strategies with site conditions and broader restoration goals to enhance the success of TDF restoration.